Integrated impacts of climate change and land use change on surface hydrology in the future in Nakdong river basin in Korea - N.V. Quan; N.Cao Don; G.S. Kim (Lowland Technology International, 2018)
The main objective of this paper is to forecast the integrated impacts of both climate change and land use changes on surface hydrology which is focused particularly on streamflow assessment under scenarios (A2, B1, and A1B) of climate change and land use change (2030, 2050, and 2080) in Nakdong basin by combination of both models as hydrology model (ArcSWAT) and land use change model (CA_Markov). The results indicated that the mean annual integrated impacts of climate change and land use change on streamflow in the future showed an increase tendency for all periods under scenarios A2, B1, and A1B. However, B1 scenario showed the highest of +3.97%, while A2 showed the lowest increase of +1.1%. However, the mean months of streamflow showed different changes that were forecasted large changes as an increase from +12 to +18% in months of Jan, Feb, Jul and Aug, while it showed a significant reduction from -9.0% to -19% in May and Oct for all periods under A2, B1, and A1B scenarios. Moreover, results were also to reveal that land use change and climate change both increased on the mean annual streamflow, but the impact of climate change was higher than that of land use change.